Simulation and experimental investigations of semi-active suspension control for passenger car - 392591 Mohd. Khairolnizam Abd. Jalil (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan Mekanikal (Automotif)) - Universiti Teknologi Malaysia, 2006